2021
DOI: 10.1021/acsnano.1c04895
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Isolation-Inspired Ultrafine CoSe2 for High-Energy Aluminum Batteries with Improved Rate Cyclability

Abstract: Transition-metal selenides are attractive cathode materials for rechargeable aluminum batteries (RABs) because of their high specific capacity, superior electrical properties, and low cost. To overcome the associated challenges of low structural stability and poor reaction kinetics, a spatial isolation strategy was applied to develop RAB cathodes comprising ultrafine CoSe 2 particles embedded in nitrogen-doped porous carbon nanosheet (NPCS)/MXene hybrid materials; the two-dimensional NPCS structures were deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…[264,265] Rizwan et al revealed the physical parameter changes related to the doping effect of MXene. [62] After Nb-doped MXene, the c-lattice parameter is enhanced (from 19.2 to 23.4 Å), the bandgap is reduced [263] Copyright 2021, American Chemical Society. b) Rate capability of different Ag content; Comparison of c) charge density distribution function of states (PDOS) of N-Ti 3 C 2 (OH) x and pristine Ti 3 C 2 (OH) x .…”
Section: Supercapacitormentioning
confidence: 99%
See 4 more Smart Citations
“…[264,265] Rizwan et al revealed the physical parameter changes related to the doping effect of MXene. [62] After Nb-doped MXene, the c-lattice parameter is enhanced (from 19.2 to 23.4 Å), the bandgap is reduced [263] Copyright 2021, American Chemical Society. b) Rate capability of different Ag content; Comparison of c) charge density distribution function of states (PDOS) of N-Ti 3 C 2 (OH) x and pristine Ti 3 C 2 (OH) x .…”
Section: Supercapacitormentioning
confidence: 99%
“…developed a N‐doped porous carbon nanosheet (NPCS)/MXene hybrid material using a spatial isolation strategy. [ 263 ] The synergistic effect of Co adsorption affinity of different N‐doping sites and MXenes is demonstrated, demonstrating a high‐energy Al‐ion battery (212 mAh g –1 after 500 cycles at 1 A g –1 ) ( Figure a). [ 263 ]…”
Section: Applications Of Heteroatom Doped Mxenes Materialsmentioning
confidence: 99%
See 3 more Smart Citations